Van fabels en feeste tot gewels en geeste : opgedra aan Pieter W. Grobbelaar - Burden, Matilda; Van der Merwe, Hennie; Grobbelaar, Pieter W.(Pieter Willem) (Stellenbosch : Stellenbosch University, 2012)
Dedicated to Pieter W. Grobbelaar.